Leading Teams #1: Introduction - Laura L. Greenhaw; Sarah A. Bush; Carrie N. Baker (EDIS)
This is the first publication on a series on leading teams. This introduction describes why teamwork is necessary, the challenges and benefits, and the difference between groups and teams. We briefly describe group development models that will be described through the remaining publications in the series.